Trends in the Introductory Communication Course from 1956 to 2016: A Systematic Review of the Results of 11 National Survey Studies - Sherwyn P. Morreale (Central States Communication Association, 2020)
Researchers have conducted surveys of the introductory communication course for more than 60 years, starting with two seminal studies in 1956 and 1965, followed by a series of nine replicative studies extending from 1970 to 2016. This systematic review examines the results from those 11 surveys. The results of that review are presented here, including historical trends observed in the thematic categories that indicate how the course has remained consistent or changed during the time period of the surveys. This study concludes with recommendations to inform decision-making about the future of the introductory course, based on the identified historical trends as well as impact factors in the context of higher education today.